Late-glacial Coleoptera fauna from Lismore, Nova Scotia - Miller, Randall; Morgan, Alan (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
Fossil Coleoptera from a late-glacial site near Lismore, Nova Scotia record paleoclimatic and paleoecological conditions prior to the Younger Dryas in eastern Canada. A buried peat deposit dated 11,900 years B.P. near the base and 10,500 years B.P. at the top contains a small insect fauna that includes both boreal species, such as Olophrum consimile, and subarctic beetle species like Elaphrus lapponicus. Although a palynological study of the Lismore site shows evidence of the Younger Dryas, the beetle fauna is poorly preserved in sandy peat deposits dated younger than 10.600 years B.P.